ACHIEVEMENT GAP BETWEEN MEN AND WOMEN IN HIGHER EDUCATION - Raushan Kumar Singh (International Journal of Multidisciplinary Research and Studies, 2021)
Policies and programmes for development that do not address gender inequality miss out on crucial chances for growth. The education of females is critical not only for reasons relating to social fairness but also due to the fact that it hastens the process of social transformation. It is imperative for the growth of human resources that gender equality be promoted within the educational system. When you educate a woman, you are really teaching her entire family. An educated woman is more capable of taking care of the health, nutrition, and education of her children, and more so of being an active actor in the social and economic growth of the country. This is because a woman bears the duty of the entire family on her own. It should come as no surprise that educational achievement is a critical factor in economic success everywhere. Literacy is the foundational skill that every student must possess. It is an essential element in the formation of both social cohesiveness and a sense of national identity. It leads to an improvement in the breadth and quality of public opinion, as well as to a more active engagement of the marginalised in the democratic process. No culture has ever achieved economic, political, or social liberation without first establishing a solid basis of educated women, and no society ever will. Education has a direct bearing on the empowerment of women because it enables women to become more knowledgeable about their rights, their skills, and the options and possibilities that are open to them. Studies have shown that there is a strong correlation between female education and a variety of developmental indicators, including increased economic productivity, improvement in health, delayed age at marriage, lower fertility, increased political participation, and effective investments in the next generation. Some of these indicators include.